Educational neoliberalization: the mediatization of ethical assertions in the voucher debate. Issue 2 (4th March 2019) - Malin, Joel R.; Hardy, Ian; Lubienski, Christopher
ABSTRACT: This study focuses on the evolving ethical claims and empirical evidence being advanced within U.S. media relating to voucher-style programs. As such, the research seeks to better understand how and why these policies proliferate, despite scant evidence recommending them. Our specific media focus reflects the recognition that issues, problems, and solutions are defined and set within 'ethical' frameworks through the media, often in efforts to influence the polity. Framed by the concept of 'neoliberalization', the analysis notes dominant discourses and activities by both advocates and opponents around the issue. Specifically, the research reveals shifting ethical assertions. Media-based 'choice for all' advocacy, and support of generalized parent choice/empowerment via voucher reforms, have become more prominent, while advocacy related to expanding choice for the disadvantaged has receded (though with certain high-profile exceptions). Meanwhile, opponents engage in what sometimes appears as more reactionary, though still active, media participation in seeking to challenge such reforms.